Antibacterial Effects of Some Antiseptics and Disinfectants - Saha, AK; Haque, MF; Karmaker, S; Mohanta, MK (Journal of Life and Earth Science, 2011)
Antimicrobial effects of six antiseptics and disinfectants were studied against five pathogenic bacteria. Different pathogens responded differently to different antiseptics and disinfectants. Antibacterial effects of the antiseptics and disinfectants were also concentration dependent. Formalin and hydrogen peroxide were highly effective against all the pathogens used while phenyl and iodine were least effective. Dettol and Savlon showed moderate antibacterial effects. Key words: Antiseptics; disinfectants; pathogen; sensitivity. DOI: 10.3329/jles.v3i0.7440 J. Life Earth Sci., Vols. 3-4: 19-21, 2009